Risk factors of incontinence-associated dermatitis among critically ill patients: A systematic review and meta-analysis - Jiang, Hongzhan; Shen, Jiali; Lin, Huihui; Xu, Qiuqin; Li, Yuanchan; Chen, Lijuan (Frontiers in Medicine, 2023)
Objectives Incontinence-associated dermatitis (IAD) is increasingly found among critically ill patients, but the risk factors for IAD in these patients are currently unclear. The purpose of this meta-analysis was to identify the risk factors of IAD in critically ill patients. Methods Web of Science, PubMed, EMBASE, and Cochrane Library were systemically searched until July 2022. The studies were selected based on inclusion criteria, and data were independently extracted by two researchers. The Newcastle-Ottawa Scale (NOS) was used to assess the quality of the included studies. Odds ratios (ORs) and their associated 95% confidence intervals (CIs) were used to identify significant differences in the risk factors. The I2 test was used to estimate the heterogeneity of studies, and Egger's test was used to assess the potential publication bias. Results A total of 7 studies enrolling 1,238 recipients were included in the meta-analysis. Age ≥ 60 (OR = 2.18, 95% CI: 1.38~3.42), female sex (OR = 1.76, 95% CI: 1.32~2.34), dialysis (OR = 2.67, 95% CI: 1.51~4.73), fever (OR = 1.55, 95% CI: 1.03~2.33), vasoactive agent (OR = 2.35, 95% CI: 1.45~3.80), PAT score ≥ 7 (OR = 5.23, 95% CI: 3.15~8.99), frequency of bowel movement > 3times/d (OR = 5.33, 95% CI: 3.19~8.93), and liquid stool (OR = 2.61, 95% CI: 1.56~4.38) were the risk factors of IAD among critically ill patients. Conclusions Many risk factors are related to IAD among critically ill patients. Nursing staff should pay more attention to evaluating the risk of IAD and enhance the care of high-risk groups.